The Prevalence of Microorganisms in H1N1 Patients Compared to Seasonal Influenza in a Sample of Iraqi Patients - Yasir A. Atahia; Kadhim A. Kadhim (College of Pharmacy University of Baghdad, 2017)
This study provides valuable information on secondary microbial infections in H1N1 patients compared to Seasonal Influenza in Iraqi Patients. Nasopharynx  swabs were collected from  (12 ) patients  infected with Seasonal influenza (11  from Baghdad  and 1 Patient from south of Iraq) ,and ( 22 ) samples from patients with 2009 H1N1 ( 20 from Baghdad and  2 from  south of Iraq). The results show that the patients infected with 2009 H1N1 Virus were younger than healthy subjects and those infected with seasonal influenza. And the difference reached to the level of significance     (p< 0.01) compared with healthy subjects.Two cases infected with 2009 H1N1 virus (9.1%) were from south of the Iraq and remaining 20 cases were from Baghdad . Polymicrobial isolates from nasopharynx swab were observed in patients infected with 2009 H1N1 virus. Polybacterial infections (2-7 microorganisms) and fungal infection were reported in 21 out of 22 patients (95.5%) and 5 out of 22 (22.7 %) respectively.The predominant isolated microorganisms were Streptococcus pyogenes , Staphylococcus aureus and Streptococcus pneumoniae  were found in 95.2 %  , 95.2 % and 90.5 %  respectively .The results also show  that seven microorganisms were isolated from 10 (47.6 %) patients infected with 2009 H1N1 , no microorganism was isolated from patients infected with seasonal influenza or healthy persons. Key words: Seasonal Influenza , 2009 H1N1, Nasopharynx  swabs